Financial burden of colorectal cancer treatment among patients and their families in a middle-income country - Azzani, Meram; Roslani, April Camilla; Tin, Tin Su (Springer Verlag (Germany), 2016)
Background: In Malaysia, the healthcare system consists of a government-run universal healthcare system and a co-existing private healthcare system. However, with high and ever rising healthcare spending on cancer management, cancer patients and their families are likely to become vulnerable to a healthcare-related financial burden. Moreover, they may have to reduce their working hours and lose income. To better understand this issue, this study aims to assess the financial burden of colorectal cancer patients and their families in the first year following diagnosis. Methods: Data on patient costs were collected prospectively in the first year following diagnosis by using a self-administered questionnaire and telephone interviews at three time points for all four stages of colorectal cancer. The patient cost data consisted of direct out-of-pocket payments for medical-related expenses such as hospital stays, tests and treatment and for non-medical items such as travel and food associated with hospital visits. In addition, indirect cost data related to the loss of productivity of the patient and caregiver(s) was assessed. The patient’s perceived level of financial difficulty and types of coping strategy were also explored. Result: The total 1-year patient cost (both direct and indirect) increased with the stage of colorectal cancer: RM 6544.5 (USD 2045.1) for stage I, RM 7790.1 (USD 2434.4) for stage II, RM 8799.1 (USD 2749.7) for stage III and RM 8638.2 (USD 2699.4) for stage IV. The majority of patients perceived paying for their healthcare as somewhat difficult. The most frequently used financial coping strategy was a combination of current income and savings. Conclusion: Despite the high subsidisation in public hospitals, the management of colorectal cancer imposes a substantial financial burden on patients and their families. Moreover, the majority of patients and their families perceive healthcare payments as difficult. Therefore, it is recommended that policy- and decision-makers should further consider some financial protection strategies and support for cancer treatment because cancer is a very costly and chronic disease.